2019
DOI: 10.1002/jcb.29513
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐7 promotes neural differentiation of trabecular meshwork mesenchymal stem cell on nanofibrous scaffold

Abstract: The purpose of this study was to investigate miR‐7 overexpression effects on neural differentiation of mesenchymal stem cells (MSCs) on both two‐dimensional (2D) and three‐dimensional (3D) culture systems. We upregulated miR‐7 through lentiviral vector in trabecular meshwork MSCs (TMMSCs) and polymers of poly l‐lactic acid/polycaprolactone fibrous scaffold were fabricated by electrospinning and characterized using scanning electron microscopy (SEM) and Fourier transform infrared (FTIR). Neural markers expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Previous studies have reported that mirna-217-5p regulates pluripotent stem cell proliferation and differentiation (17) and is involved in metabolic processes in various cells, such as endothelial (18) and colorectal cancer (19) cells. These findings provide insights into the application of miRNAs in regenerative and cell therapy for muscle diseases (14). However, a limited number of studies have explored the potential roles of mir-217-5p in SkMScs.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous studies have reported that mirna-217-5p regulates pluripotent stem cell proliferation and differentiation (17) and is involved in metabolic processes in various cells, such as endothelial (18) and colorectal cancer (19) cells. These findings provide insights into the application of miRNAs in regenerative and cell therapy for muscle diseases (14). However, a limited number of studies have explored the potential roles of mir-217-5p in SkMScs.…”
Section: Introductionmentioning
confidence: 84%
“…accumulating evidence suggests that a number of micrornas (mirnas), such as mir-99a-5p (10), mir-9-5p (11), mir-208b (12), serve important roles in skeletal muscle myogenesis by regulating gene expression, and that their abnormal expression is associated with a number of muscle diseases including, muscle atrophy and ischemic injury (6,13,14). regarding the molecular mechanism of mirnas in myogenesis, studies have reported a role for these molecules in the differentiation of SkMScs (13,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of nanoscale to submicrometre topographic features on influencing TM cell alignment, migration and gene expression has been investigated in several studies [ 53 , 95 , 96 , 97 ]. Similar observations were noted: a loss of in vivo characteristic cell properties when cultured on tissue culture plastic or planar surfaces, such as myocillin [ 98 ], and TM/stem cell expression [ 53 ] and stabilisation of these necessary in vivo markers in the presence of randomised nanopatterns.…”
Section: Current Biomaterials Approaches To Modelling the Tm/escmentioning
confidence: 99%
“…It was illustrated that presence of these specific patterns had retained myocillin and verscian protein expression in comparison to TM cultures grown on tissue culture plastic or aligned surfaces [ 95 , 96 ]. This has led other studies to look deeper into the manipulation of TM cells through topographical features, with electrospun, non-aligned, nano-fibrous scaffolds containing poly L-lactic acid/polycaprolactone improving the differentiation of TM cells into glial and neural progenitor cells [ 97 ]. In addition to the embedding of TM cells into Matrigel ® , a BM mixture that is rich in nanotopographical features [ 101 ] was deemed favourable for the expansion and manipulation of human TM cells into adipocytes, chondrocytes and endothelial cells [ 52 , 53 ].…”
Section: Current Biomaterials Approaches To Modelling the Tm/escmentioning
confidence: 99%